Struggles against any system of domination - Mojica Mendieta, Francisco Javier (2021)
Latin America and the Caribbean are witnessing in 2021 the struggles "against all systems of domination". This expression was raised by Elisa Loncon, Mapuche leader, on July 4, 2021 after being elected as president of the Constitutional Convention in Chile to draft a new Magna Carta, and with it, eradicate the legacy of the dictatorship of Augusto Pinochet from Chile. In recent history, these struggles were originated, first, by the high school student rebellion of the "Penguins" in October 2019 but which has a precedent of more than three five years and then, by other social movements that led to a process to draft a new constituent. This expression, in my opinion, synthesizes the historical struggle of the peoples of Latin America and the Caribbean against racism, genocide, slavery, patriarchy, phallocentrism, androcentrism, the capitalocene seen from the approach of the unequal world-ecology (Moore 2013a, 2013b, 2020; Navarro and Machado, 2020) and the coloniality of power, knowledge and nature. Theoretically, this editorial is approached from critical theory and methodologically, through literature review and dialogue with social activists and academics of the continent that allow me to make a brief review of the core conflicts of a few countries in the region. In these pages I hope to show different forms of resistance and creativity to re-found and propose alternatives to the long-standing modern colonial world system -more than 500 years old.